Emergence of KPC-2 and NDM-13-coproducing carbapenem-resistant hypervirulent Klebsiella pneumoniae with high-risk sequence type ST11 - Tao, Jia; Wang, Liru; Yang, Na; Fu, Hui; Hu, Xinxin; Lai, Tingyu; Jin, Jianning; Li, Gang (Frontiers in Microbiology, 2025)
BackgroundCarbapenem-resistant hypervirulent Klebsiella pneumoniae (CR-hvKp) co-producing KPC and NDM poses serious threats to public health. This study aimed to elucidate the molecular mechanisms underlying the resistance and virulence of a clinical CR-hvKP isolate coproducing KPC-2 and NDM-13 in China.MethodsThe K. pneumoniae strain A51998714 was isolated from a 58-year-old male patient in China in June 2024. MALDI-TOF/MS was used to species identity. Antimicrobial susceptibility testing was determined using the VITEK-2 system. Whole-genome sequencing (WGS), plasmid conjugation assays, and plasmid stability testing were conducted to characterize resistance and virulence determinants. Virulence potential was assessed using serum-killing assays.ResultsThe CR-hvKp strain A51198714 exhibited resistance to nearly all tested antibiotics, including ceftazidime-avibactam and aztreonam. PCR and Sanger sequencing confirmed the co-occurrence of blaKPC-2 and blaNDM-13. WGS analysis revealed that strain A51198714, belonging to ST11-K64, possessed a single chromosome and five plasmids. Virulence-associated genes, localized on the IncHI1B plasmid pA51998714-VIR and the chromosome, were linked to enhanced colonization and infectivity. The serum-killing assay showed strain A51998714 was resistant to serum killing. The blaKPC-2, blaCTX-M-65, and blaTEM-1 genes were located on an IncFII plasmid pA51998714-KPC. The blaNDM-13 gene was located on plasmid pA51998714-NDM, which was classified as IncI1-I type. Conjugation assay and plasmid stability testing showed that plasmid pA51998714-NDM can be successfully transferred and maintained stably in the host.ConclusionThis study reports a clinical ST11-K64 CR-hvKP strain co-producing KPC-2 and NDM-13, which carried multiple resistance genes on two resistant plasmids, along with virulence factors enhancing its pathogenicity. These findings underscore the imperative for enhanced surveillance to mitigate the dissemination of such high-risk, multidrug-resistant, and hypervirulent strains.